The Legal Consequences of Heirs Not Submitting the Notary Protocol To The Regional Supervisory Board - Dinda Suryo Febyanti; Fanny Tanuwijaya; Echwan Iriyanto (Jurnal Ilmu Kenotariatan, 2023)
The legal issue faced by heirs who do not submit a notary's protocol when a notary passes away. Although Indonesian law does not explicitly outline the responsibilities of heirs in this regard, based on this, the research subject to be examined is the legal consequences for heirs who do not submit a notary's protocol and the authority of the Regional Supervisory Board in resolving notary protocols. The research method used in this study is a notarial juridical approach, using a legislative approach and a conceptual approach to analyze the legal issues. The research findings indicate that the failure to submit a notary's protocol can have negative legal consequences. Notary protocols, considered as state archives, must be preserved and maintained by notaries, and heirs do not have legal rights to them. The duty to submit notary protocols lies with the Regional Supervisory Board for documentation processes. These protocols include agreements, deeds, acknowledgments, and legal acts performed before a notary and are not part of the notary's personal estate but belong to the state. The authority of the Regional Supervisory Board in handling the handover of notary protocols. The MPD plays a vital role in receiving reports of notary deaths, facilitating the handover process, and ensuring the preservation of protocols. However, there are no specific sanctions that the MPD can impose on heirs who fail to fulfill their obligations. This legal gap may result in violations by heirs who do not report the notary's death or fail to submit the notary protocol. Therefore, this research emphasizes the importance of establishing clear and comprehensive regulations regarding the responsibilities of heirs regarding notary protocols to ensure legal certainty and clarity for all parties involved. KEYWORDS: Legal Consequences, Heirs, Notary Protocol Submission, Regional Supervisory Board